Muhammadiyah Bugis-Makassar: Dispersal of Muslim Organizations in and from South Sulawesi, Indonesia - Halim, Wahyuddin; Nubowo, Andar (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2025)
This study examines the dispersal of Islamic authority within Muhammadiyah in South Sulawesi and how local cultural values influence Islamic reformism. It highlights the emergence of new organizations such as Darul Istiqamah, Hidayatullah, and Wahdah Islamiyah, founded by Muhammadiyah activists with distinct institutional paths. These organizations emerged through ideological shift, cultural entrepreneurship, and political opportunity. Bugis-Makassar values, particularly siri’ (shame and dignity) and pessé/paccé (solidarity), promote independent leadership and institutional creation over internal compromise. Drawing on political opportunity, resource mobilization, and sectarianization theories, the study shows that religious authority dispersal is shaped by local socio-cultural logics. The Darul Islam movement’s legacy further supports more rigid reformist visions. Rather than fragmentation, this process reflects culturally mediated adaptation and innovation. The concept of “Muhammadiyah Bugis-Makassar” illustrates how local cultural dynamics catalyze Islamic reform into networked activism, where regional values reshape organizational boundaries and influence broader Islamic movements. This framework offers insights into cultural mediation of Islamic reform trajectories across Indonesia.